2022
DOI: 10.32322/jhsm.1176813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of culture-positive and culture-negative severe infectious keratitis leading to hospitalization: a tertiary referral center experience

Abstract: Aim: To compare the predisposing factors, surgical interventions, length of hospital stay (LOHS), and treatment outcomes of culture-positive (CP) versus culture-negative (CN) severe infectious keratitis (IK) resulting in hospitalization in a tertiary referral clinic. Material and Method: We retrospectively reviewed the medical and microbiological records of 287 patients clinically diagnosed with severe keratitis over a 4-year period. Results: Of 287 study participants, 141 (49.1%) had positive CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[31][32][33] These discrepancies may be attributed to variations in demographic data and risk factors among the study populations. 29,31 In our study, we found that the median direct cost for treating a single episode of severe keratitis was US$10,840.17, with an interquartile range spanning from US$5866.56 to US$24,172.28. Notably, there was no significant difference in direct costs observed between cases with negative cultures and those with positive cultures.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…[31][32][33] These discrepancies may be attributed to variations in demographic data and risk factors among the study populations. 29,31 In our study, we found that the median direct cost for treating a single episode of severe keratitis was US$10,840.17, with an interquartile range spanning from US$5866.56 to US$24,172.28. Notably, there was no significant difference in direct costs observed between cases with negative cultures and those with positive cultures.…”
Section: Discussionmentioning
confidence: 63%
“… 31–33 These discrepancies may be attributed to variations in demographic data and risk factors among the study populations. 29 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation